2008
DOI: 10.1080/13590840802150845
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of biosynthesis of endogenous 17‐B oestradiol by boron supplementation: One possible role of dietary boron consumption in humans

Abstract: Background. Recent evidence indicates that boron has a widespread role in biochemistry and nutrition and may have anti-carcinogenic properties. It interacts with calcium, vitamin D and magnesium, which are all important in bone metabolism. Boron also increases steroid hormone concentrations in animals and humans and hints at a role in the prevention of chronic diseases such as osteoporosis, arthritis and other steroid hormone dependent diseases. It has been suggested that the interaction between boron and ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…Based on recent clinical data, this is the first human study report to show an increase level of free testosterone after boron consumption. Previously, supplementation of healthy males with 10 mg/d after several weeks resulted in a significant rise in plasma 17-B estradiol concentration [17] and the increase was consistent with some animal reports, as well [18,19]. It was shown that changes in plasma testosterone is achievable by boron in rats [20] and also in rats fed a range of dietary boron for 30 or 60 days, which appear to be time-and dose-dependent [21].…”
Section: Variablesupporting
confidence: 75%
“…Based on recent clinical data, this is the first human study report to show an increase level of free testosterone after boron consumption. Previously, supplementation of healthy males with 10 mg/d after several weeks resulted in a significant rise in plasma 17-B estradiol concentration [17] and the increase was consistent with some animal reports, as well [18,19]. It was shown that changes in plasma testosterone is achievable by boron in rats [20] and also in rats fed a range of dietary boron for 30 or 60 days, which appear to be time-and dose-dependent [21].…”
Section: Variablesupporting
confidence: 75%
“…Boron may also help prevent bone-related diseases such as osteoporosis, arthritis, and other steroid hormone dependent diseases, possibly by improving absorption of calcium, phosphorus, and magnesium and retention of calcium and magnesium [42]. Although the role of boron in bone metabolism remains unclear, a current hypothesis implicates hydroxylation of estrogen [39]. Similarly, another track considered by biochemists is that formation of boroesters with ribose-derived compounds can influence reactions involving S-adenosylmethionine and oxidized nicotinamide adenine dinucleotide (NAD + ) [43].…”
Section: Boronmentioning
confidence: 98%
“…Data suggest a beneficial interaction occurs between boron and steroid hormones involved in bone metabolism [39][40][41]. Indeed, 17␤-estradiol appears to be a target, such that its concentration and efficacy are enhanced by boron, improving trabecular bone volume, bone growth plate density, and trabecular separation [41].…”
Section: Boronmentioning
confidence: 99%
“…7 Similar significant increase in serum E2 levels was found in healthy males after 4 weeks of boron supplementation. 14 Therefore, one possible proposed mechanism is the conversion of T to E2 by boron.…”
mentioning
confidence: 99%
“…It was speculated that alterations in steroid hormone concentrations by boron may have an impact on stone removal. Fourteen (14) volunteer patients whose urolithiasis was confirmed by ultrasonography method were referred and admitted to receive a 10-mg boron supplement per day in the form of capsules. The capsules were formulated and provided by a pharmacist colleague, using sodium tetraborate as the source of boron.…”
mentioning
confidence: 99%